The effects of soda cracker preparation on the Vitamin A content of fortified wheat flour - Cortez, Miguel Brigido J.; Tabardillo, Joyce Abigail A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study was conducted to evaluate the effect of soda cracker preparation on the amount of vitamin A from fortified flour. Vitamin A concentration was determined in raw fortified and unfortified flour as well as flour mixtures from different stages in soda cracker preparation including mixing of ingredients, rolling of the dough, and baking. The soda cracker from the developed recipe was found to be acceptable after consumer testing. The study found that the amount of vitamin A (dry basis) in fortified flour (3.17 ± 0.524 𝜇gRE/g) was significantly higher (p<0.05) than in unfortified flour (0.593 ± 0.161 𝜇gRE/g). Despite causing an observed vitamin A loss in fortified flour, all steps in soda cracker preparation were found not to have a significant effect (p>0.05) on the vitamin A content of fortified flour. On the other hand, mixing, rolling and baking were observed to decrease the vitamin A content of unfortified flour. The vitamin A content (dry basis) of fortified and unfortified flour mixtures after processing was observed to be 3.05 ± 0.137 𝜇 gRE/g and 0.369 ± 0.0532 𝜇 gRE/g respectively, which is higher compared to literature values of soda crackers. Vitamin A content of fortified flour after processing exceeded expected values. Water activity, moisture content, and pH of flour and flour mixtures were also found to change throughout preparation of soda crackers.
submitted July 2017
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Enriched foods